Truth about burnout : how organizations cause personal stress and what to do about it - Maslach, Christina (Jossey-Bass Publishers San FranciscoUS, 1997)
Suggests and describes causes of burnout at the workplace, including: work overload, lack of control, insufficient reward, and breakdown in the sense of belonging. Examines the consequences of burnout and advocates the need for management to address the issue seriously. Suggests approaches for eradicating the problems that trigger burnout.